DISFEMIA DALAM KOLOM HUKUM DAN KEADILAN KORAN RAKYAT KALBAR PERIODE OKTOBER SAMPAI DESEMBER 2016 - Hidayanti, Reztari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research is focused on disfemia on Rakyat Kalbar newspaper in column law and justice on October?December in 2016. There were 92 columns of law and justice in October?December in 2016. This research is conducted for people as readers, to be able to know the purpose of the use of disfemia on newspaper. The result of this research shows that the form of disfemia language found as words and the number of the words found are (120 words). The words found which are basic words are (20 words), affixed words are (87 words), repeated words are (eight words), and compound words are (five words). The disfemia sense values found are mengerikan, menyeramkan, menakutkan, menjijikan, dan menguatkan rasa. There is disfemia in column law and justice on Rakyat Kalbar newspaper that has 1 sense value, but there is also disfemia which has two sense values. The planning of this research implementation in Bahasa Indonesia lesson can be conducted on the eleventh grade of vocational high school (SMK). The appropriate curriculum with this research is the curriculum of 2013 with Basic Competence (KD) 3.3 Analyze the historical story text, news, advertisement, editorial/opinion, and fiction story in the novel, spoken or written. Keywords: disfemia, newspaper, language form, and sense value.